2012
DOI: 10.1371/journal.pone.0038384
|View full text |Cite
|
Sign up to set email alerts
|

SOCS2-Induced Proteasome-Dependent TRAF6 Degradation: A Common Anti-Inflammatory Pathway for Control of Innate Immune Responses

Abstract: Pattern recognition receptors and receptors for pro-inflammatory cytokines provide critical signals to drive the development of protective immunity to infection. Therefore, counter-regulatory pathways are required to ensure that overwhelming inflammation harm host tissues. Previously, we showed that lipoxins modulate immune response during infection, restraining inflammation during infectious diseases in an Aryl hydrocarbon receptor (AhR)/suppressors of cytokine signaling (SOCS)2-dependent-manner. Recently, In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 34 publications
2
43
0
1
Order By: Relevance
“…Public T-cell clones express TCR sequence motifs shared by different individuals, and are often expanded by immunization, infection, or autoimmunity (McBerry et al, 2012; Venturi et al, 2008). To study the role of public repertoires in zebrafish, we defined a public sequence as one appearing in at least two different individuals, as previously defined in other studies (Li et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Public T-cell clones express TCR sequence motifs shared by different individuals, and are often expanded by immunization, infection, or autoimmunity (McBerry et al, 2012; Venturi et al, 2008). To study the role of public repertoires in zebrafish, we defined a public sequence as one appearing in at least two different individuals, as previously defined in other studies (Li et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Because of these limitations, it is still unclear what fraction of the potential T-cell repertoire is expressed, and how similar are the repertories of different individuals in the quiescent state and during the course of an immune response. In addition, TCR sequences shared by different individuals (termed public TCR sequences) are detected in all vertebrates in multiple biological contexts, a surprising finding when the number of potential unique CDR3 sequences generated by VDJ recombination is considered (McBerry et al, 2012; Venturi et al, 2008). However, the significance of public TCRs on the repertoire, as well as their response to stimulation is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Another set of interesting genes identified encodes TNF-receptor associated factor (TRAF)-like proteins (AT5G26290, AT3G20370, AT5G26260, AT5G52330, and AT1G582700), identified by both microarray metaanalysis and RNA-seq. The TRAF-like genes are a large gene family in Arabidopsis encoding potential E3 ligase proteins (Huang et al, 2004;Gingerich et al, 2007;McBerry et al, 2012), only a very few of which have been functionally characterized. These genes may play a role in the regulation of protein turnover in response to cytokinin.…”
Section: Discussionmentioning
confidence: 99%
“…However, preincubation with LXA4, to some extent, inhibited the TRAF6 synthesis induced by LPS in NHEKs. Some studies demonstrated that LXA4-induced AhR activation and its subsequent nuclear translocation lead to SOCS2 expression, TRAF6 Lys47-linked poly-ubiquitination and proteosome-mediated degradation of the adapter proteins [17] . It was also reported that LXA4, signaling through ALXR and AhR, mediates innate and acquired immune responses via induced expression of SOCS2 [8] .…”
Section: Discussionmentioning
confidence: 99%
“…McBerry et al recently reported that TRAF6 is degraded by both LXA4 and L-kynurenine via an SOCS2-dependent pathway [17] . Our hypothesis is that whether SOCS2/TRAF6 are involved in the anti-inflammation process of LXA4 in keratinocytes.…”
mentioning
confidence: 99%